Investigation on microwave absorption characteristics of conductive-coated honeycomb absorber. (15th June 2020) - Choi, Jae-Hun; Jang, Min-Su; Jang, Woo-Hyeok; Kim, Chun-Gon
Abstract: Because microwave absorbers are limited in their absorption performance and bandwidth by their thickness, research on lightweight microwave absorbers having a wide bandwidth has been increasingly conducted. Lightweight structures with periodicity, such as honeycomb structures, have been increasingly attracting attention as they have the potential for application as lightweight broadband absorbers. Aramid or glass fiber-based honeycomb cores are dielectric materials that are often used in industrial applications. If a honeycomb absorber is manufactured by coating a conductive material on a honeycomb core, microwave absorption performance can be expected in a wide frequency range. However, structures with a certain periodicity, such as honeycombs, may bring about unexpected effects due to the shape with respect to the propagation direction of the microwave. In this study, the characteristics of absorbing electromagnetic energy in honeycomb absorbers were investigated, and the possibility of analyzing honeycomb absorbers by the transmission line analysis method was examined. Based on this investigation, a honeycomb absorber was fabricated, and the simulation results were verified by evaluating the performance by the free-space measurement method. Because of unpredictable scattering of the microwave polarized in the in-plane direction, for honeycomb absorbers, it is necessary to keep the coating resistance low or carefully consider the influences through simulation.